Relationships among atmosphere-cryosphere-biosphere in a transitional glacial catchment (Sabbione Lake, North-Western Italian Alps) - COLOMBO, NICOLA; FRATIANNI, SIMONA; Giaccone E.; Paro L. (Naaim-Bouvet F., Durand Y. and R. Lambert, 2013)
The present study was carried out in the Sabbione Basin (North-Western Italian Alps, Piedmont). Climatological and geomorphological studies were conducted in order to understand the relationships among climate change and its effects on cryosphere and geosphere. Meteorological data (air temperature, rain and snow) recorded by two stations in the studied area (Formazza and Sabbione) were analyzed. Considering its importance in the cryosphere, particular attention to snow data (amount of snowfall, thickness and persistence of snow cover) was paid; moreover, some stratigraphic profiles of snow cover and snow density data (from A.I.N.E.V.A. and Meteomont, respectively interregional agency and military service for snow and avalanches) were examined. A detailed geomorphological map (scale 1:10000) was created from multitemporal photographic interpretation of aerial images and digital orthoimages. Moreover, field surveys were conducted with the aim to identify micromorphological evidences resulting from cryotic processes. In order to determine the potential presence/absence of permafrost in the area, the model PERMACLIM was implemented in a plug-in in open GIS (QuantumGIS software), and modelled meteorological data input (air temperature and, especially, snow thickness and distribution) were analyzed in detail through the comparison with ground measured data and satellite images. The geomorphological analysis results were compared with three permafrost distribution models, already available for the studied area (PERMAROCK mod., APMOD and Swiss Permafrost Map). Finally, floristic surveys were carried out in order to characterize the vegetation in the basin.